Autoeficácia docente na inclusão de estudantes com deficiência intelectual - Paganotti, Emille Gomes (Universidade Federal de São Carlos, 2021)
Social Cognitive Theory (SCT) understands self-efficacy as a predictor of actions and behaviours adopted by people for a specific demand and context. Teaching activity is a specific occupation and is influenced by this construct. This research aimed to analyze the role of teaching self-efficacy in the inclusion of students with intellectual disabilities (ID) from a formative action based on collaborative consulting. Three elementary school teachers participated. The research is collaborative, that is, it is a process of joint construction. This process involves the teaching practice to students with intellectual disabilities and theoretical knowledge and reflections mediated by the researcher. First, we performed ethical procedures and the preparation of fieldwork. After the proper approvals, the research began with the elaboration, application and evaluation of a collaborative consulting program for the inclusion of students with intellectual disabilities. The instruments for data collection were: a questionnaire to characterize the participants and their actions for inclusion, a questionnaire to assess the Núcleo Comum, Escala de Eficácia Docente para Práticas Inclusivas de educandos com Deficiência Intelectual (EEDPI-DI), Protocolo de Observação de Situações Educacionais, Escala de Fontes de Autoeficácia Docente (EFAED) and a final evaluation questionnaire of the collaborative consulting program. The results showed that collaborative consulting proved to be an important strategy for promoting self-efficacy, especially during online teaching because of Covid-19 pandemia. There was an increase in self-efficacy perceived in all teachers who completed the collaborative consulting program. The sources of self-efficacy that were most evident in the teachers’ speeches were vicarious experience and social persuasion. The observation of models and study of contents about school inclusion were fundamental for building the perception of capacity and ability to include students with ID. The data also showed that feedback on the teaching work performed was an important element that can affect positively or negatively the actions achieved by the teachers. Based on the results found, this thesis discusses continuing teacher training for teachers whose goal is to include students with ID in regular classrooms. We also discussed the sources of self-efficacy present in the speeches of the teachers during their participation in the collaborative consulting program. This study has limitations, especially due to the small number of participants, whose data should not be generalized. Despite this situation, we believe that the relevance of this research is to produce knowledge about the role of self-efficacy of teachers to design strategies for the inclusion of students with ID in the studied city, considering the complexity and variability of situations and contexts where teaching is present. For future studies, we suggested the replication of the program developed here on a larger scale. In addition, the replication could be carried out with teachers from the final years of basic education. Moreover, this collaborative consulting program should be offered online, which may include professors from other Brazilian states.
Teacher’s self-efficacy in the inclusion of students with intellectual disabilities
Keywords: Educação especial; Autoeficácia; Docentes; Deficiência intelectual; Consultoria colaborativa; Special needs education; Self-efficacy; Teacher; Intellectual disabilities; Collaborative consultation; CIENCIAS HUMANAS::EDUCACAO